Skew-tolerant dynamic logic circuits - Ong, Chi Boon. (2008)
This dissertation discusses the overhead of traditional domino logic that consumes a higher cycle time. It also discusses the objective of skew-tolerant circuit design that includes the static and domino circuits. The advantage of skew-tolerant design is to avoid solid edges in which the data must meet the setup time before a clock edge. Apart from this, skew-tolerant domino circuits also use multi-overlapping clocking to reduce latches and thus eliminating solid edges and minimize the sequencing overhead.